Economic Order Quantity Inventory Considering Perishable Factor in Product, Delay in Payment, All-Unit Discount, and Product Return - Roland Y. H. Silitonga; Hanafi Kartawirawan; Siham Bouguern (Engineering Science Letter, 2022)
The inventory existence of the company is a waste but still needed to maintain service level. For drug industry companies, especially pharmaceutical installations, the expiration factor is a factor that needs to be considered because drugs have an expiration date. Previous research has an inventory model that considers product expiration factors, permissible payment delays, and price discounts. The developed study provides a solution to the loss of expiry costs by adding a return factor. This research aims to create an inventory model that considers expiration factors, permissible payment delays, discounts, and product returns. The result of the developed model can minimize the total cost of inventory by 3.37% with the predefined parameters compared to the previous model, which has not considered the return factor.